Do Women give up Competing more easily? Evidence from the Lab and the Dutch Math Olympiad - Thomas Buser; Huaiping Yuan (Tinbergen Institute, 2016)
We conduct three lab experiments and use field data from the Dutch Math Olympiad to study how the gender gap in willingness to compete evolves in response to experience. The main result is that women are more likely than men to stop competing if they lose. In the Dutch Math Olympiad, this means that girls who do not make the top 1000, and therefore do not advance to the next round, are less likely to compete again one year later while there is no effect on boys. In an additional experiment, we show that men are more likely than women to start and keep competing after receiving positive feedback. In a third experiment, we show that the gender difference in the reaction to losing is not present when winning and losing are random rather than the outcome of competition. The fact that women are more likely to give up competing after a setback may help to explain why fewer women make it to the top in business and academia.
Keywords: C91; D03; J01; J16; 330; willingness to compete; gender; feedback; career decisions; laboratory experiment